2022
DOI: 10.1186/s12978-022-01545-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends and socio-demographic components of modern contraceptive use among sexually active women in Rwanda: a multivariate decomposition analysis

Abstract: Background The attainment of targets set for modern contraceptive use remains a challenge in sub-Saharan Africa. Rwanda, in its new Family Planning and Adolescent Sexual Reproductive Health/Family Planning (FP/ASRH) Strategic Plan 2018–2024 has set the attainment of a contraceptive prevalence rate (CPR) of 60% by 2024. To achieve this, identifying factors that enhance modern contraceptive use among sexually active women is critical. Methods We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The finding of this study, which show that education played a key role in contributing to the observed change in contraceptive use in Zambia resonates with what has been reported in prior studies conducted in Rwanda, Ethiopia, Kenya and Cameroon [ 12 , 17 , 60 , 61 , 66 ]. This observation potentially suggests that educated women are more likely to make informed decisions on their reproductive health by adopting contraceptive use.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding of this study, which show that education played a key role in contributing to the observed change in contraceptive use in Zambia resonates with what has been reported in prior studies conducted in Rwanda, Ethiopia, Kenya and Cameroon [ 12 , 17 , 60 , 61 , 66 ]. This observation potentially suggests that educated women are more likely to make informed decisions on their reproductive health by adopting contraceptive use.…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that change in contraceptive use was mainly as a result of changes in women’s contraceptive behaviour. However, the finding that 15% of the increase in contraceptive use in Zambia was explained by differences in women’s characteristics is lower compared to what was found in Ethiopia (34%), Cameroon (69%) and Rwanda (23%) [ 12 , 17 , 61 ]. The variations in population structure and socio-economic characteristics of women in the study countries may account for the disparity in the observed changes in CPR across different counties.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Teenagers who live in rural areas and are from poorest households had an increase in teenage pregnancy over the four surveys analysed for this study. This finding could be explained by inadequate access to SRH information and low contraception use among young teenager from rural areas and those from poor communities [ 9 , 10 , 23 , 33 ]. The increase in the trends of teenage pregnancy was also observed among those illiterate and married/formerly married teenage women.…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus in literature that access to family planning education influences reproductive outcomes such as age at first sex, contraception, age at first birth, teenage pregnancy and fertility preference among women of reproductive age [ 16 21 ]. Given the observed high levels of fertility in SSA [ 6 , 8 , 22 ], family planning education campaigns have focused on disseminating messages on benefits of smaller family sizes on both maternal and child health.…”
Section: Introductionmentioning
confidence: 99%